Oligoribonuclease is an essential component of the mRNA decay pathway - Ghosh, Sandip (The National Academy of Sciences, 1999)
mRNA decay in prokaryotic cells involves the action of both endo- and exoribonucleases. In Escherichia coli, degradation of RNA to the mononucleotide level was thought to depend on RNase II and polynucleotide phosphorylase. Here, we show that the enzyme oligoribonuclease is an essential part of this process as well. Thus, inactivation of the orn gene encoding oligoribonuclease leads to a cessation of cell growth. Moreover, although pulse-labeled RNA decays normally in orn mutant cells under nonpermissive conditions, a large fraction of the resulting products is small oligoribonucleotides rather than the mononucleotides generated in wild-type cells. The oligoribonucleotides that accumulate are 2–5 residues in length; longer molecules disappear during the decay process. These data indicate that oligoribonuclease is required to complete the degradation of mRNA to mononucleotides and that this process is required for cell viability. Inasmuch as close homologues of the orn gene are found in a wide range of eukaryotes, extending up to humans, these findings raise the possibility that oligoribonuclease also participates in mRNA degradation in these organisms.